The role of law and ethics in the globalized economy - Straus, Joseph (MPI studies on intellectual property, competition and tax law, 2009)
The subprime crisis and the general crisis of the global financial system in 2008 not only put the globalization process and all that it involves under extreme pressure, but, at least for some, it called the entire system into question. What in spring had seemed unthinkable, at least for those who had ignored Paul Krugman's blogs, suddenly and without warning became hard reality. A credo of today's prominent leaders is that thoroughly considered and internationally effective regulation is needed to address almost all current global challenges, whether they concern global warming, human rights and migration, or international finance. Such regulatory systems will have to pay attention to ethics and morals, which is something that the present collapsed system has failed to do. This book privides insight into the functioning of the global economy, the rotts of the present international financial crisis and the responses of highly distinguished politicians, industrialists and academics. (Quelle: Text Verlagseinband / Verlag)